Money, not protection. Assisted return programmes and the timing of future harm in refugee status determination - Feneberg, Valentin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Originally established as an alternative to deportation after a failed asylum application, Assisted Return programmes have increasingly become a significant factor in the asylum procedure. By analysing an extensive body of case law from German courts, this article demonstrates how these programmes are primarily used to argue that life-threatening deprivation upon return is too unlikely to warrant international protection. Only a few courts contend that these programmes do not sufficiently protect against deprivation. This disagreement stems from conflicting assessments of the programmes’ effectiveness and differing interpretations of the timing of future harm. The prevalent requirement that harm must be imminent upon return aligns with the judicial expectation that asylum seekers are responsible for availing themselves of return assistance, bringing about their own ‘deportability’. It also leads to inadequate fact-finding regarding the actual effects of Assisted Return programmes. Monetary support through return programmes is thus considered as an alternative to protection, or at least facilitates its rejection. Given the original purpose of the programmes to increase the number of returnees among rejected asylum seekers, this demonstrates how policy measures have effects beyond their initial scope, and how judges indirectly implement policy.
Keywords: Refugee Status Determination; Assisted Return Programme; Court; Poverty; Country of Origin Information